2020
DOI: 10.1021/acs.jpcb.0c00061
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond Solvation Response and Partial Viscosity Decoupling of Solute Diffusion in Ionic Acetamide Deep Eutectic Solvents: Fluorescence Up-Conversion and Fluorescence Correlation Spectroscopic Measurements

Abstract: Fluorescence up-conversion (∼250 fs instrumental response) coupled with time correlated single photon counting measurements was performed to explore the complete Stokes shift dynamics of a dipolar solute probe, coumarin 153 (C153), in several ionic acetamide deep eutectic solvents (DESs) that contained lithium nitrate/bromide/perchlorate as electrolyte. Combined measurements near room temperature reflected a total dynamic Stokes shift of approximately 800−1100 cm −1 and triexponential solvation response functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…Hydrogen bonded networks (HBN) exist in pure HBDs, and these networks are characterized by unique local and supramolecular dynamics 21 23 . Moreover, in lithium salt and amide-based DESs, Kaur et al and Subba et al confirmed the existence of spatial and temporal nanoscale heterogeneity, respectively, which likely results from segregated ionic and HBD domains 24 , 25 . However, the evolution of such heterogeneities in DESs with composition as well as their resulting influence on macroscopic transport properties of DESs remain poorly understood.…”
Section: Introductionmentioning
confidence: 94%
“…Hydrogen bonded networks (HBN) exist in pure HBDs, and these networks are characterized by unique local and supramolecular dynamics 21 23 . Moreover, in lithium salt and amide-based DESs, Kaur et al and Subba et al confirmed the existence of spatial and temporal nanoscale heterogeneity, respectively, which likely results from segregated ionic and HBD domains 24 , 25 . However, the evolution of such heterogeneities in DESs with composition as well as their resulting influence on macroscopic transport properties of DESs remain poorly understood.…”
Section: Introductionmentioning
confidence: 94%
“…[74][75][76] Many researchers have also used FCS exclusively for the measurement of the translational diffusion of different probe molecules in DESs and RTILs, which provides information regarding the extent of solute-solvent association and the local environment of the medium. 29,52,[74][75][76][77][78] Therefore, in the present investigation, FCS studies have also been performed to get a better understanding of the probes' diffusion dynamics and intermolecular solutesolvent interaction at a single molecular level. Fig.…”
Section: Fluorescence Correlation Spectroscopic (Fcs) Studiesmentioning
confidence: 99%
“…Mixtures of Li salts and amides are characterized by a well-studied micro-heterogeneity. 11,130,[138][139][140] The investigation of electrolytes composed Li salts (LiClO4, LiBr, LiNO3) with AA and other short-chain amides (propionamide PA and butyramide BA) via time-resolved fluorescence measurements and all-atom MD simulation revealed for instance pronounced solution heterogeneity. 11,130 In all cases the AA−ion interactions are stronger than the AA−AA ones.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%